Synthesis and Characterization of Some Transition Metal Complexes of Benzyl 2-((1E, 4E)-1, 5-Bis (2-Nitrophenyl) Penta-1, 4-Dien-3-Ylidene) Hydrazinecarbodithioate - Nabeel Arif Tawfeeq (International Journal of Scientific Research in Science and Technology, 2025)
A new Schiff base was synthesized from S-benzyldithiocarbazide and di-para-nitrobenzal acetone. Besides, five new divalent transition metal complexes were also synthesized according to the published articles in this field. The new compounds were fully characterized using different characterization instruments. The results which are obtained from different characterization tools were fit with theoretical values. The metal complexes obtained consist of one transition metal and two ligands.
Keywords: S-benzyldithiocarbazide; Schiff base; metal complexes; symmetrical ketone; di-p-nitrobenzalacetone